2019
DOI: 10.5114/bta.2019.90237
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the biosynthesis of renewable polyhydroxyalkanoate copolymer containing 3-hydroxyvalerate by Massilia haematophila using statistical modeling

Abstract: Polyhydroxyalkanoate (PHA) is a microbial storage polymer that is naturally produced by certain bacteria. This is the first study on the ability of this particular species Massilia haematophila to synthesize a PHA copolymer containing 3-hydroxyvalerate (3HV) monomer. Using the statistical design on Massilia haematophila UMTKB-2, this study highlights the optimization of poly(3-hydroxybutyrate-co-3-hydroxyvalerate), P(3HB-co-3HV), copolymer production for shaken-flask cultivation. Moreover, the mechanical and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The marine sponge-associated bacterial diversity profiling revealed that eight out of the ten most dominant genera and four out of the ten most dominant families were previously published PHA producers ( Figure 7 ) [ 51 , 52 ]. However, not all species classified as PHA-producing genera are experimentally shown to produce PHA.…”
Section: Resultsmentioning
confidence: 99%
“…The marine sponge-associated bacterial diversity profiling revealed that eight out of the ten most dominant genera and four out of the ten most dominant families were previously published PHA producers ( Figure 7 ) [ 51 , 52 ]. However, not all species classified as PHA-producing genera are experimentally shown to produce PHA.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the PHA accumulation process of Cupriavidus sp. that ends within 48-72 h, 122 h was needed for optimum P(3HB-co-3HV) accumulation by M. haematophila UMTKB-2 [89] (Table 2).…”
Section: Alkyl Alcohol-tolerant P(3hb-co-3hv)-producing Bacteriamentioning
confidence: 99%
“…The primary sources of MGB pure cultures were predominantly obtained from the regions of East Asia, South East Asia, and South Asia and extensively identified in various habitats ( Table 1 , Supplementary Tables S1A , S1B ) using 16S rRNA-based amplicon sequencing analysis. The distribution of MGBs includes high-salt sludges ( Li et al, 2019 , 2020 ; Yin et al, 2022 ), tannery effluent ( Lian et al, 2016a , b ; Sanjay et al, 2020 ), brackish water ( Kiun et al, 2016 ), mangrove rhizosphere sediment (BioProject no PRJNA682484), farm soil ( Zhang et al, 2015 ), shrimp aquaculture farm ( Joseph et al, 2014 ), storage tanks containing biodiesel ( White et al, 2011 ), water droplets from within the bitumen ( Himmelberg, 2019 ), geothermal lake (MYI strain CEMTC_1,393, GenBank accession no. OP143686.1), and pond (“Shoubuike”) ( Fujita et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments employed nutrient-rich media to facilitate the growth of MGBs, including bacto marine broth, LB broth supplemented with 15% (v/v) glycerol ( Zhang et al, 2015 ), LB agar ( Behera et al, 2017 ), brain heart infusion agar ( Sanjay et al, 2020 ), and a medium consisting of meat extract, yeast extract, and peptone ( Kiun et al, 2016 ). These nutrient-rich media are not recommended due to their inability to eradicate undesirable microbial flora effectively.…”
Section: Introductionmentioning
confidence: 99%